ANALISIS PRODUKTIVITAS MESIN MOULDING PADA PT PLASMOTECH BATAM - Nola kesmonita; Paskaria Loyda Tarigan, Elsya (Computer Science and Industrial Engineering, 2023)
PT Plasmotech Batam is a company engaged in the field of injection molding by producing plastic components for the needs of connectors, capacitors, electronics and automotive. One of the molding machines used is the rotary engel machine. Machines that are used continuously result in equipment or machines being damaged resulting in long downtime and decreased machine productivity. The purpose of this research is to find out how to reduce downtime to increase machine productivity, while the method used is Overall Equipment Effectiveness (OEE). This study measures OEE values during November 2021-April 2022 and uses six big looses and analyzes these values using a fishbone diagram to find the root of the problem. The results showed that the OEE value was 87.35%, and the biggest six big loose value was equipment failure of 6.87% so that the company could increase machine productivity from the focus of the problem.